Handling, restraint and administration of subcutaneous and intramuscular injections for the cat. - American Institute of Biological Sciences; Communication Skills Corporation (American Institute of Biological Sciences. Released by Communication Skills Corp., 1974)
Shows how to handle, restrain, and administer subcutaneous and intramuscular injections to cats in the laboratory.
With study guide.
Keywords: Cats as laboratory animals; Injections, Hypodermic; Injections, Intramuscular; Animal immobilization